Sumbangan produktiviti keseluruhan terhadap pertumbuhan output industri skel kecil dan sederhana (IKS) di Malaysia - Ismail, Rahmah; Chai, Nyet Fung (Universiti Utara Malaysia, 2002)
In Malaysia, small and medium-scale industries (SMls) comprise about 90 per cent of the total manufacturing establishments. However, contribution of SMIs to the manufacturing value added is quite low at about 26 per cent. This is partly attributed to low level of productivity and eficiency and less capability of SMIs to gain economies of scale. In this respect, SMIs cannot merely rely on physical inputs like capital and labour in the course to raise their value added but must enhance the contribution oftotal factor productivity (TFP). TFP refers to a gain in additional output as a result of enhancement infirms' eficiency. An increase in the contribution of TFP will lead a decrease in cost of production and hence,firm will be more competitive. This article attempts to analyse to what extent TFP growth contributes to SMls' output growth. Analysis in this article separates SMIs by size, namely, small-scale industry (SSls) and medium-scale industries (MSls). In each industrial size, the analysis will compare TFP contribution by sub-industries. Analysis is based on the six selected subindustries, namely, food, beverage, wood-based, chemical, rubber-based and non-metallic mineral products. The data for the analysis is obtained from the Manufacturing Industrial Survey, Department of Statistics, Malaysia for the period of 1981-1994. Analysis is based on the estimation results of the production function using stochastic frontier approach, whereby TFP is divided into two parts, namely, technical efficiency and technological progress.